2018
DOI: 10.1111/rego.12187
|View full text |Cite
|
Sign up to set email alerts
|

Agencies’ formal independence and credible commitment in the Latin American regulatory state: A comparative analysis of 8 countries and 13 sectors

Abstract: This article tests functional and institutional explanations for the different levels of formal independence of regulatory agencies in Latin America. The analysis is grounded in an original database of the formal independence level of 104 regulators in 8 countries and 13 regulatory sectors. The results challenge a central claim of the credible commitment hypothesis as they indicate that privatization is not a significant determinant of agency independence nor are utility regulators more likely to be independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
2
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 62 publications
5
23
2
6
Order By: Relevance
“…Previous research has observed national and sectoral patterns in the diffusion of regulatory agencies (Jordana et al, 2011;Jordana & Levi-Faur, 2005). Thus, our findings confirm Gilardi's (2002Gilardi's ( , 2005aGilardi's ( , 2008 notion of veto players' role as a functional equivalent to delegation, although some recent research indicates that this relationship may be reversed in economically less developed countries (Mediano, 2018). Finally, Model 7 includes further controls for the rule of law and length of EU membership, economic resources (GDP per capita) and size of countries (population) as well as other characteristics of the political system that might impact upon the level of regulatory autonomy granted, such as parliamentarism and the electoral system.…”
Section: Empirical Findingssupporting
confidence: 86%
See 4 more Smart Citations
“…Previous research has observed national and sectoral patterns in the diffusion of regulatory agencies (Jordana et al, 2011;Jordana & Levi-Faur, 2005). Thus, our findings confirm Gilardi's (2002Gilardi's ( , 2005aGilardi's ( , 2008 notion of veto players' role as a functional equivalent to delegation, although some recent research indicates that this relationship may be reversed in economically less developed countries (Mediano, 2018). Finally, Model 7 includes further controls for the rule of law and length of EU membership, economic resources (GDP per capita) and size of countries (population) as well as other characteristics of the political system that might impact upon the level of regulatory autonomy granted, such as parliamentarism and the electoral system.…”
Section: Empirical Findingssupporting
confidence: 86%
“…In Model 6, a hypothetical move from a country without any veto player to a country with full political constraints on policy change is associated with a 0.663-unit decrease (on a zero to one scale) in regulatory autonomy. Thus, our findings confirm Gilardi's (2002Gilardi's ( , 2005aGilardi's ( , 2008 notion of veto players' role as a functional equivalent to delegation, although some recent research indicates that this relationship may be reversed in economically less developed countries (Mediano, 2018). At least for European countries, the number of veto players seems to reduce the need not only for formal independence but also for the subdimension of regulatory autonomy.…”
Section: Empirical Findingssupporting
confidence: 85%
See 3 more Smart Citations